2018
DOI: 10.24875/ric.17002395
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of a Black Bean (<I>Phaseolus vulgaris</I> L.) Extract and its Flavonoid Fraction in Both in vitro and in vivo Models of Lymphoma

Abstract: BBE and FF had cytotoxic action by driving OCI-Ly7 cells into apoptosis as well as blocking progression to G2/M phase. In addition, BBE and FF treatments were effective in xenograft models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Likewise, flavonoids from black soybean hulls can inhibit the proliferation of lymphoma cells. In addition, after exposure to this compound, the cells underwent apoptosis and the cell population in phase‐S increased (Aregueta‐Robles et al., 2018). In recent years, there have been many studies regarding anthocyanins and flavonoids in black soybean hulls, while the role of soluble dietary fibers (SDFs) from black soybean hulls was rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, flavonoids from black soybean hulls can inhibit the proliferation of lymphoma cells. In addition, after exposure to this compound, the cells underwent apoptosis and the cell population in phase‐S increased (Aregueta‐Robles et al., 2018). In recent years, there have been many studies regarding anthocyanins and flavonoids in black soybean hulls, while the role of soluble dietary fibers (SDFs) from black soybean hulls was rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…These evidences suggest that diet may be a risk factor or a preventive agent for lymphomas. Indeed several natural or synthetic products (Menezes et al, 2016;Aregueta-Robles et al, 2018;Ye et al, 2018) are reported to reduce the risk of certain types of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that phenolic and flavonoids that are derived from plants exhibit potent anti-inflammatory activity by regulating the concentration of various inflammatory cytokines or mediators such as cyclooxygenase-2 (COX-2), tumor necrosis factor (TNF-α), and nuclear factor-kappa (NF-κB), interleukin 1, interleukin 6, interleukin 10, nitric oxide (NO), lipoxygenase (LOX), and iNOS [8]. Flavonoids isolated from black bean hulls can affect cell cycle by inducing cell cycle arrest at the S-phase and preventing progression to G2/M stages, as well as causing activation of apoptosis on OCI-Ly7 lymphoma cells in mouse [57]. In another experiment, phytosterol treatment reduces the development of production of carcinogens, inhibits cell growth, and also promotes apoptosis in cancer cells [10].…”
Section: Anticancer Activitiesmentioning
confidence: 99%